Development of Sea Gurp Caulerpa Sp Culture in The Ytr Letman Tour Islands of Central Maluku - Erbabley, Nally Y.G.F.; Amahorseja, Anggeline; Kelabora, Dominggas M.; Tutratan, Filemon; Leploi, Andreas; Silubun, Yanru; Mukhlis, Mukhlis (Unram Journal of Community Service, 2024)
To maintain the cultivation of sea grapes while developing the tourism potential of the YTR area, an effort is needed to develop a sea grape cultivation area that provides unique value and new experiences to visitors or tourists how to learn to love the environment, especially aquatic ecosystems through educational tourism. The goal is to conserve sea grape resources that have economic value for the community and increase public awareness of the availability of resources in nature, train students to apply the knowledge gained in lectures to the community and build an entrepreneurial spirit from an early age. The training provided to the community consisted of: 1). Entrepreneurship counselling; 2). Training on making cultivation containers (quadrant nets) and sea grape cultivation (lat) to support educational tourism in the YTR area. The construction of sea grape cultivation containers in the form of frames / quadrants was carried out by Polikant students, then the results were socialised to the Letman community and the YTR Pokdarwis group and then worked together at the cultivation site in the YTR tourist area. The evaluation results showed positive feedback from the community and the product was developed into one of the souvenirs of the YTR Letman tourist